2022
DOI: 10.3389/fpsyg.2022.925195
|View full text |Cite|
|
Sign up to set email alerts
|

Does creative thinking contribute to the academic integrity of education students?

Abstract: The current research focuses on the nature of the relationship comprising personality traits, creative thinking, and academic integrity. Scholars have confirmed that personality traits and creative thinking correlate positively with academic integrity. However, a discussion of academic integrity, personality traits, and creative thinking is missing in the scholarly literature. This study used a questionnaire survey based on the Big Five Factor to identify personality characteristics, the Academic Integrity Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 77 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, 68% of these admitted to committing serious acts of dishonesty, including cheating on exams or in the submission of written papers and essays. Eshet and Margaliot (2022) provide additional evidence, finding that 71% of the students surveyed admitted to cheating during their preservice teacher training. Despite these high rates, a significant disconnect in perception exists, with many not considering academic dishonesty a serious issue, deeming such incidents as "rare" or "occasional" (Daniel et al, 1991).…”
Section: Prevalence and Perceptionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, 68% of these admitted to committing serious acts of dishonesty, including cheating on exams or in the submission of written papers and essays. Eshet and Margaliot (2022) provide additional evidence, finding that 71% of the students surveyed admitted to cheating during their preservice teacher training. Despite these high rates, a significant disconnect in perception exists, with many not considering academic dishonesty a serious issue, deeming such incidents as "rare" or "occasional" (Daniel et al, 1991).…”
Section: Prevalence and Perceptionmentioning
confidence: 88%
“…A significant aspect in the perception of academic dishonesty is the influence of observing dishonest behaviour among peers. Studies show that future teachers are more likely to admit to engaging in similar behaviours if they perceive their peers have done so (Eshet & Margaliot, 2022;Unal, 2011). Moreover, more negative attitudes or perceptions toward academic dishonesty are associated with a lower incidence of these behaviours, indicating that attitudes toward academic integrity can predict their perpetuation (DiPaulo, 2022;Fontaine et al, 2020).…”
Section: Prevalence and Perceptionmentioning
confidence: 99%
“…Furthermore, it has become clear that HyFlex and hybrid pedagogy will continue beyond the COVID-19 era [ 42 , 43 ]. It has been shown that unethical academic behaviour could lead to undeveloped credentials or skills, thus resulting in professional incompetence, which would severely affect the validity of learning and the broader application of learning in future professional life [ 26 , 44 , 45 ]. Hence, studying the prevalence of academic dishonesty in the HyFlex learning environment will become ever more important, as will developing strategies to prevent it.…”
Section: Introductionmentioning
confidence: 99%
“…However, when graduate students engage in fewer innovative behaviors and cannot fulfill their academic or research goals, some may resort to academic misconduct driven by internal and external motivations ( Krou et al, 2021 ; Yu and Zhang, 2021 ). Previous research has found that creative thinking has a positive impact on academic integrity, and education in creative thinking can reduce the occurrence of academic misconduct ( Eshet and Margaliot, 2022 ). There are also studies that theoretically suggest that insufficient innovative capability among graduate students, resulting in an inability to produce valuable research outcomes, directly leads to academic misconduct ( Su and Wang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%